PERBANDINGAN NILAI TOTAL PLATE COUNT (TPC) DAN CEMARAN Salmonella sp. PADA IKAN TONGKOL (Eutynnus sp.) YANG DIJUAL DI TEMPAT PELELANGAN IKAN (TPI), PASAR TRADISIONAL DAN PEDAGANG IKAN ECERAN DI KOTA KUPANG - Priska Clayu Apelabi; Diana A. Wuri; Maxs Urias E Sanam (JURNAL KAJIAN VETERINER, 2019)
Tuna is one of the fishery products which has a high level of consumption in the city of Kupang but are easily damaged. One of the pathogenic bacteria in fish that cause food-borne disease is Salmonella sp. The contamination of Salmonella sp. is caused by inadequate sanitation, poor hygiene and contaminated water used by the merchant. This study aims to determine both the differences in the value of TPC and whether there is the contamination of Salmonella sp. or not. Moreover, this study was to examine quantification of contamination level and different levels of Salmonella sp contamination the difference level of Salmonella sp. contamination in tuna fishes which has been sold in the fish auction place (TPI), traditional markets and retail fish market in Kupang. 54 samples of Tuna were collected from three locations. This research was also supported by the water quality testing which consisted of 15 water samples. The result showed that there was a significant difference on the TPC values with an average level of contamination from the highest to the lowest, started from the fish retailers as many as 1,35 x 105 CFU/g, followed by the traditional markets as many as 5 x 104 CFU/g and TPI as many as 3,5 x 103 CFU/g. The differences of TPC values were due to the personal higyene and sanitation, locations, the equipments as well as the materials used in the post-arrest process, the distribution and the sales. The results from TPC analysis showed that 4 samples were contaminated by the Salmonella sp. The average level of Salmonella sp contamination was from the Tuna sold by the fish relailers as many as 1,6 x 102 followed by the traditional fish markets as many as 1 x 102 and in the TPI as many as 4x10. This study also showed that based on water quality test, positive results were found in 1 sample in TPI, 3 samples in the traditional markets and 4 samples in the fish retailers. In conclusion, the Tunas sold by the fish retailers have the highest TPC value and the highest level of Salmonella sp contamination compare to the Tunas sold in the traditional markets and TPI.